2016
DOI: 10.1002/ece3.2133
|View full text |Cite
|
Sign up to set email alerts
|

Winners and losers: tropical forest tree seedling survival across a West African forest–savanna transition

Abstract: Forest encroachment into savanna is occurring at an unprecedented rate across tropical Africa, leading to a loss of valuable savanna habitat. One of the first stages of forest encroachment is the establishment of tree seedlings at the forest–savanna transition. This study examines the demographic bottleneck in the seedlings of five species of tropical forest pioneer trees in a forest–savanna transition zone in West Africa. Five species of tropical pioneer forest tree seedlings were planted in savanna, mixed/tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 68 publications
(155 reference statements)
3
31
0
Order By: Relevance
“…Saplings have better developed root systems, are taller, and have higher leaf area and carbohydrate reserves than seedlings. Unfavorable climate conditions and competition will affect their growth rates, but not necessarily their survival (Cardoso et al 2016). Belowground competition grasses can slow sapling growth particularly during periods of higher than average rainfall (February et al 2013) or if mineral availability is increased (Vadigi and Ward 2012) and can also be amplified by browsing (Vadigi and Ward 2014).…”
Section: Transitioning From Saplings To Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Saplings have better developed root systems, are taller, and have higher leaf area and carbohydrate reserves than seedlings. Unfavorable climate conditions and competition will affect their growth rates, but not necessarily their survival (Cardoso et al 2016). Belowground competition grasses can slow sapling growth particularly during periods of higher than average rainfall (February et al 2013) or if mineral availability is increased (Vadigi and Ward 2012) and can also be amplified by browsing (Vadigi and Ward 2014).…”
Section: Transitioning From Saplings To Adultsmentioning
confidence: 99%
“…Among tree species of tropical Africa, seedlings that allocated resources preferentially to growth and resource-capture traits (e.g., height, leaf area, root-shoot ratios) survived better in ecotones between forests and savannas where fire frequency was low; species that allocated preferentially to carbohydrate storage in leaves and roots had better survivorship in fireprone savannas (Cardoso et al 2016). However, larger saplings survived better than smaller saplings, irrespective of allocation traits in either plant community.…”
Section: Transitioning From Saplings To Adultsmentioning
confidence: 99%
“…For example, Geiger et al [85] showed that in a Brazilian savannah -gallery forest transition not burned for 35 years, only five forest species were successfully expanding into the adjacent grassy vegetation environment. Cardoso et al [123] showed that only a few forest species are sufficiently drought-and fire-resistant to be able to survive the establishment phase in an African savannah environment.…”
Section: (F ) Biological Invasionsmentioning
confidence: 99%
“…Tree seedling shows greater mortality during dry season as compared to wet season, which may be attributed to its competition with grasses for nutrient resources (Chirara et al 1999). On the contrary, under limited or lower resource conditions, grass competition has been reported to have a less negative or even a positive role on the establishment of tree seedling during dry season (Vieira and Scariot 2006a, b;Cardoso et al 2016). Therefore, field experiments are needed to elucidate these conflicting observations and to understand how grass competition determines the tree recruitment in dry tropical environment under the effect of other set of environmental drivers.…”
Section: Grass Competitionmentioning
confidence: 99%
“…It may have serious ecological consequences, particularly under changing climate. Studies suggest that tree-seedling survival and establishment in dry tropical ecosystems are constrained mainly by water availability (Khurana and Singh 2001;Kraaij and Ward 2006;Cardoso et al 2016), nutrient availability (Bardgett and Wardle 2003;Vadigi and Ward 2013), shade (Gerhardt 1996;Khurana and Singh 2001), and grass competition (Griscom et al 2014). Therefore, tropical tree species may have considerably poor productivity under resource-limited conditions (e.g., inadequate water, light, and soil nutrients) and under grass competition.…”
Section: Introductionmentioning
confidence: 99%